Exploring Qualitative Descriptive Methods in Korean Linguistic Studies - Cahyo, Eko Nur; Darmanto, Darmanto; Muliawan, Anugrah Adi; Maulidita, Salismi Zulfi; Masruroh, Siti (CV. Tripe Konsultan, 2025)
The current research aimed to uncover the use of the descriptive qualitative method in Korean linguistic studies, with the main objective of investigating how this method is applied in such research. This study is not merely theoretical but also practical, as it provides guidelines for conducting research in Korean linguistics using descriptive qualitative approaches. The objects of this study were scholarly articles and relevant books, as well as previous research reports selected through purposive sampling, analyzed using a qualitative approach with a library research method and documentation techniques for data collection. The findings reveal six stages in conducting Korean linguistic research with descriptive qualitative methods: problem identification, literature review, determining research objectives, data collection, data analysis and interpretation, and reporting of findings. Furthermore, data analysis involves four essential steps, namely data collection, data reduction, data display, and drawing conclusions. Although the descriptive qualitative method proves beneficial for research in Korean linguistics, it still presents challenges, particularly the potential subjectivity of researchers during data interpretation. Therefore, this research suggests that future studies should be supported by alternative perspectives, such as quantitative methods or a mixed-methods approach that combines both quantitative and qualitative methodologies in linguistic research.